Human Resource Practices and Organizational Performance - Aggarwal, S. S. (Gyan Management Journal, 2010)
This paper investigates the relation between the Human Resource practices and the performance of corporations if HR practices is made multi-dimensional and also is treated as an endogenous variable. It has become clear that firm performance has important implications for employees and organizations as confirmed by past researchers. This is imperative in order to ensure the successful management of employees and also to improve productivity and achievements of an organization. It was found that incentive is positively related to organizational performance but did not moderate the relationship between both HR practices and organizational performance.